Mental health, violence, suicide, self-harm, and HIV in series and films of Netflix: content analysis and its possible impacts on society - Peña, Mikel; Sarrionandia, Ainize (Frontiers in Communication, 2023)
The media entertainment we consume significantly affects our behavior, our relationships, and our identity. Thus, this study focuses on some of the main problems of society today and analyzes how these variables are represented on Netflix. Specifically, this study analyzes how content related to mental health, violence, suicide, self-harm, and Human Immunodeficiency Virus (HIV) appears in the ten most-watched movies and ten most-watched series on Netflix. To this end, a conceptual analysis method based on a 5-minute interval coding is used. Results posit that violence is shown in 38.7% of the movie sections and 37.3% of the series. Suicide and self-harm appear, respectively, in 0.9% and 0% of the movies and 1.3% and 0.2% of the series. Regarding mental health, 0.5% of the analyzed individuals had a mental health diagnosis. Finally, none of the 220 main characters analyzed stated that they had HIV. Among the conclusions, the need to regulate violence in the media or to mitigate the impact it generates should be highlighted. Likewise, mental health, suicide, selfharm, and HIV have been observed not to have a realistic representation in fiction, which generates stigmatization.